Burnout on Contact Center: A Literature Review - Fulaedzah, Indah Asrin (International Journal Labs, 2022)
Background: The use of contact centers is considered the most effective way to love relationships with customers. Contact centers are proven to improve service to customers and reduce operational costs. On the other hand, high pressure causes contact center employees to be vulnerable to burnout.Aim: This study aims to find out what factors can cause burnout. The method used is review literature.Method: The researcher implemented a systematic review. The articles used in this study was obtained from the website of scientific database providers google schoolar and ScienceDirect using keyword burnout, contact centers, contact centers, call centers, call centers. Article inclusion criteria are journals or fulltext open access articles published in 2016-2021 and produce 8 articles.Findings: The results of this review obtained factors that can cause burnout in contact center employees in general consist of sociodemographic factors, internal factors and external factors such as age, gender, emotional intelligent, mindfulness, characteristics, responsibilities, and workload, as well as conflicts that employees have.